EDUKASI PENGELOLAAN SAMPAH DI SEKITAR SUNGAI DESA MOJOSARIREJO: EDUKASI PENGOLAHAN, KEBIJAKAN, ORGANISASI DAN INFRASTRUKTUR - Rachmania Widya Ningrum; Yhasinta Agustyarini; Akhmad Fauzi; Agung Purwono; Nurul Azizah Ria Kusrini (Universitas Al-Amien Prenduan, 2023)
The river problem faced by Mojosarirejo village, specifically in Pudo, is a problem for the last five years that has not been resolved properly. Rivers with lots of rubbish disrupt the irrigation process of rice fields. So it is necessary to carry out various analyzes to solve this problem. The method used is PAR, which includes several tools that are the focus of the discussion in this article, namely mapping, transectural, ranking, historical tracing, trend and change, and program strategy analysis. This Community service aims to facilitate community problems (in managing waste around rivers) which are obtained from the community and resolved by the community. With several analyzes and PAR methods used, program results were obtained consisting of four elements. First, there is cleaning of the river environment and education about waste management. Second, the existence of institutions or organizations and policies in waste management. Third, there is infrastructure such as trash cans as TPS. Fourth, there is literacy insight for the public regarding waste decomposition in the form of educational boards. The suggestion in this research is that the community can carry out the four programs initiated and have larger land as a landfill.